Removal of ammonium ion from aqueous solution using natural Turkish clinoptilolite - Karadag, Dogan; Koc, Yunus; Turan, Mustafa; Armagan, Bulent (ELSEVIER SCIENCE BV, 2006)
A study on ion exchange kinetics and equilibrium isotherms of ammonium ion on natural Turkish clinoptilolite (zeolite) was conducted using a batch experiment technique. The effects of relevant parameters, such as temperature, contact time and initial ammonium (NH4+) concentration were examined, respectively. The pseudo first-order, pseudo second-order kinetic models and intraparticle diffusion model were used to describe the kinetic data. The pseudo second-order kinetic model provided excellent kinetic data fitting (R-2 > 0.990) and intraparticle diffusion effects ammonium uptake. The Langmuir and Freundlich models were applied to describe the equilibrium isotherms for ammonium uptake and the Langmuir model agrees very well with experimental data. Thermodynamic parameters such as change in free energy (Delta G(0)), enthalpy (Delta H-0) and entropy (Delta S-0) were also determined. An examination of the thermodynamic parameters shows that the exchange of ammonium ion by clinoptilolite is a process occurring spontaneously and physical in nature at ambient conditions (25 degrees C). The process is also found to be exothermic. The results indicate that there is a significant potential for the natural Turkish clinoptilolite as an adsorbent material for ammonium removal from aqueous solutions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ammonium; ion exchange; clinoptilolite; isotherm; kinetic model; thermodynamic parameter; REACTIVE DYES; HEAVY-METALS; WASTE-WATER; ZEOLITE; ADSORPTION; SORPTION; EXCHANGE; BLUE; Engineering; Environmental Sciences & Ecology